2019
DOI: 10.1111/tbed.13099
|View full text |Cite
|
Sign up to set email alerts
|

Diversified sources for human infections by Salmonella enterica serovar newport

Abstract: Salmonella enterica Newport (S. Newport), with phylogenetic diversity feature, contributes to significant public health concerns. Our previous study suggested that S. Newport from multiple animal‐borne routes, with distinct antibiotic resistant pattern, might transmit to human. However, their genetic information was lacking. As a complement to the earlier finding, we investigate the relationship between each other among the hosts, sources, genotype and antibiotic resistance in S. Newport. We used the multilocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 16 publications
4
31
0
Order By: Relevance
“…Both mcr-positive (ST31) and chromosome-mediated (ST46) strains have clonal linkage with seafood origin, including tilapia and octopus. The host or sampling origin was significantly associated with the particular ST, which was suggested by our previous large-scale population study [18]. We also found an isolate from ST45, a previous bovine adaptive subclade, with colistin resistance.…”
supporting
confidence: 75%
“…Both mcr-positive (ST31) and chromosome-mediated (ST46) strains have clonal linkage with seafood origin, including tilapia and octopus. The host or sampling origin was significantly associated with the particular ST, which was suggested by our previous large-scale population study [18]. We also found an isolate from ST45, a previous bovine adaptive subclade, with colistin resistance.…”
supporting
confidence: 75%
“…Salmonella serovars have a wide host range and can be transmitted to a broad diversity of animals, including mammals, birds, fish, and insects (Pan et al, 2019). Besides, Salmonella can grow in plants and can survive in protozoa, soil, and water (Silva et al, 2014;Pan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Salmonella can grow in plants and can survive in protozoa, soil, and water ( Silva et al, 2014 ; Pan et al, 2018 ). Hence, broad-host-range Salmonella can be transmitted via feces from wild animals, farm animals, and pets or by consumption of a wide variety of common foods: poultry, beef, pork, seafood, milk, fruit, and vegetables ( Pan et al, 2019 ; Elbediwi et al, 2020 ). Phylogenomic analysis of four strains, determined in this study, with all available mcr-1 -carrying S. Typhimurium and monophasic isolates from swine, poultry, humans, and environment, showed that these four strains were closely related and clustered together with four additional Chinese pork isolates and one human isolate ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…NTS is primarily transmitted via commercial food or water. Contaminated raw products are also increasingly considered as an important vehicle for Salmonella dissemination, leading to foodborne outbreaks [13, 14]. Reptiles, numerous wildlife animals and, importantly, the environment contaminated by these can also serve as the reservoir for Salmonella [15, 16], which are usually found as phylogenetically diverse serovars and isolates [1, 17].…”
Section: Data Summarymentioning
confidence: 99%